A Research Framework to Integrate Cross-Ecosystem Responses to Tropical Cyclones. (6th May 2020) - Hogan, J Aaron; Feagin, Rusty A; Starr, Gregory; Ross, Michael; Lin, Teng-Chiu; O'connell, Christine; Huff, Thomas P; Stauffer, Beth A; Robinson, Kelly L; Lara, Maria Chapela; Xue, Jianhong; Reese, Brandi Kiel; et al.
Abstract: Tropical cyclones play an increasingly important role in shaping ecosystems. Understanding and generalizing their responses is challenging because of meteorological variability among storms and its interaction with ecosystems. We present a research framework designed to compare tropical cyclone effects within and across ecosystems that: a) uses a disaggregating approach that measures the responses of individual ecosystem components, b) links the response of ecosystem components at fine temporal scales to meteorology and antecedent conditions, and c) examines responses of ecosystem using a resistance–resilience perspective by quantifying the magnitude of change and recovery time. We demonstrate the utility of the framework using three examples of ecosystem response: gross primary productivity, stream biogeochemical export, and organismal abundances. Finally, we present the case for a network of sentinel sites with consistent monitoring to measure and compare ecosystem responses to cyclones across the United States, which could help improve coastal ecosystem resilience.